2012
DOI: 10.1152/physiolgenomics.00045.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perilipin 2 antisense oligonucleotide treatment on hepatic lipid metabolism and gene expression

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide. We previously showed that Perilipin 2 (Plin2), a member of lipid droplet protein family, is markedly increased in fatty liver, and its reduction in the liver of diet-induced obese mice by antisense oligonucleotide (ASO) decreased steatosis and enhanced insulin sensitivity. Plin2-ASO treatment markedly suppressed lipogenic gene expression. To gain a better understanding of the biological role of Plin2 in liver, we performed mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 36 publications
4
64
1
Order By: Relevance
“…Previous studies using antisense oligonucleotides targeting PLIN2 in ob/ob mice and in mice fed high fat diets suggested that SREBP target genes might be altered upon loss of PLIN2 (11,12,17). In this study, we show that both SREBP-1 and SREBP-2 target genes do indeed experience extreme alterations with loss of PLIN2.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Previous studies using antisense oligonucleotides targeting PLIN2 in ob/ob mice and in mice fed high fat diets suggested that SREBP target genes might be altered upon loss of PLIN2 (11,12,17). In this study, we show that both SREBP-1 and SREBP-2 target genes do indeed experience extreme alterations with loss of PLIN2.…”
Section: Discussionsupporting
confidence: 59%
“…Effects of Insulin Activity on SREBP Regulation-Insulin has been shown to exert effects on transcription and activation of SREBP-1c (12,51). Indeed, we observed impaired glucose tolerance for WT mice on WD.…”
Section: Journal Of Biological Chemistry 24241mentioning
confidence: 65%
See 2 more Smart Citations
“…Microarray analysis of the liver from HFD fed mice treated with antisense oligonucleotides against PLIN2 showed the increase in markers of hepatic proliferation (Afp and H19) and extracellular matrix remodeling (20). Markers of inflammation and oxidative stress were also increased in the liver of PLIN5 deficient mice on HFD (12).…”
mentioning
confidence: 98%